Acidiella longipennis Hendel, the type species of Acidiella Hendel (Diptera: Tephritidae: Trypetini), with recognition of two new allied species from Myanmar - Han, Ho-Yeon (Zootaxa, 2011)
The type species of the genus Acidiella Hendel is A. longipennis Hendel, which is known as a widely distributed species in South East Asia. Specimens of A. longipennis are rarely found in insect collections, but I was able to examine a number of Myanmar specimens collected by R. Malaise during the Swedish Expedition in 1934, and reported as A. longipennis by M. Hering in 1938. As a result, three related species were sorted out from these specimens. They look very much alike except for the dorsal abdominal patterns (difficult to see in dried specimens) and postabdominal structures. I here provide detailed descriptions of and a key to A. longipennis, A. spinipenis, sp. nov., and A. kambaitiensis, sp. nov. They are here defined as the A. longipennis species group based on a single synapomorphy: vesica of glans ventrally with 7–9 tiny spines. This is a unique characteristic never found in any other species of the tribe Trypetini as well as the family Tephritidae. I am providing this information as a starting point to refine the currently confused concept of the genus Acidiella.